Chromium, selenium, molybdenum: nutritional importance in support of pregnancy - O A Gromova; I Yu Torshin; V N Serov; T R Grishina; N K Tetruashvily (IP Berlin A.V., 2015)
Pregnancy is the special female condition. During this period, you are obliged to take care of yourself, your health, your food and drink and medications you use. It is during this period when major changes occur as well as the needs of women themselves - in fact they should supply the body with nutrients, vitamins and minerals not only themselves, but also the unborn child. Recently, of particular importance in the physiological support of pregnancy are micronutrients such as chromium, selenium and molybdenum. Chromium normalizes metabolism of sugars, prevents formation of insulin resistance, has immunomodulatory and anti-hyperlipidemic action. Molybdenum is needed for the prevention of anemia in pregnant women and the formation of congenital malformations in the fetus. Selenium is essential for nutritional periconceptual support, prevention of disorders of lipid metabolism and cholestasis, and is essential for the functioning of the thyroid gland.